Straßenverkehr und Hummeln - eine erste Bilanz. - Donath, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1989)
After an inquiry of four years it is visible, that traffic is entailing a decrease of buble-bee-pupulations of the most species. The abundance and the number of species is declining in all cases. On a comparing area the decrease is not so great. Some protective measures are suggested.